Correlate not optional: PP sprouting and parallelism in “much less” ellipsis - Jesse Harris; Katy Carlson (Glossa, 2019)
Clauses that are parallel in form and meaning show processing advantages in ellipsis and coordination structures (Frazier et al. 1984; Kehler 2000; Carlson 2002). However, the constructions that have been used to show a parallelism advantage do not always require a strong semantic relationship between clauses. We present two eye tracking while reading studies on focus-sensitive coordination structures, an understudied form of ellipsis which requires the generation of a contextually salient semantic relation or scale between conjuncts. However, when the remnant of ellipsis lacks an overt correlate in the matrix clause and must be “sprouted” in the ellipsis site, the relation between clauses is simplified to entailment. Instead of facilitation for sentences with an entailment relation between clauses, our online processing results suggest that violating parallelism is costly, even when doing so could ease the semantic relations required for interpretation.